PENGARUH METODE PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS III SD NEGERI 101932 PERBAUNGAN - Mei Sarah (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
This study aims to determine the effect of the Problem Solving method on student learning outcomes in thematic learning in class III SD Negeri 101932 Perbaungan. The population in the study were all 26 students of class III semester I. The instrument used in the study was a 10-item test in the form of a One Shot Case Study. In this study, the sampling technique used was population sampling. The results showed that the use of problem solving methods (Problem Solving) had an effect on student learning outcomes in Thematic learning, namely Theme 3 (Things Around Me) and Sub Theme 1 (Multiple Things Around Me) in class III SD Negeri 101932 Perbaungan. This is shown in the final calculation with a one-way t-test obtained tcount = 10.542. Then consulted the one-way t distribution table with dk = 26-1 = 25 and a significant level of 5% obtained t table = 1.708. In other words, the tcount value is located in the H0 rejection area. Thus tcount > ttable, the H1 hypothesis is accepted and H0 is rejected, so it can be interpreted that the Problem Solving method is effective on thematic learning outcomes, namely Theme 3 (Things Around Me) with Sub Theme 1 (Variety of Things Around Me) in class III SD Negeri 101932 Perbaungan.